Effect of cadmium on cytosine hydroxymethylation in gastropod hepatopancreas - Nica, Dragos; Popescu, Cristina; Draghici, George; Privistirescu, Ionela; Suciu, Maria; Stöger, Reinhard (Springer, 2017)
5-Hydroxymethylcytosine (5hmC) is an important, yet poorly understood epigenetic DNA modification, especially in invertebrates. Aberrant genome-wide 5hmC levels have been associated with cadmium (Cd) exposure in humans, but such information is lacking for invertebrate bioindicators. Here, we aimed to determine whether this epigenetic mark is present in DNA of the hepatopancreas of the land snail Cantareus aspersus and is responsive to Cd exposure. Adult snails were reared under laboratory conditions and exposed to graded amounts of dietary cadmium for 14 days. Weight gain was used as a sublethal endpoint, whereas survival as a lethal endpoint. Our results are the first to provide evidence for the presence of 5hmC in DNA of terrestrial mollusks; 5hmC levels are generally low with the measured values falling below 0.03%. This is also the first study to investigate the interplay of Cd with DNA hydroxymethylation levels in a non-human animal study system. Cadmium retention in the hepatopancreas of C. aspersus increased from a dietary Cd dose of 1 milligram per kilogram dry weight (mg/kg d. wt). For the same treatment, we identified the only significant elevation in percentage of samples with detectable 5hmC levels despite the lack of significant mortalities and changes in weight gain among treatment groups. These findings indicate that 5hmC is an epigenetic mark that may be responsive to Cd exposure, thereby opening a new aspect to invertebrate environmental epigenetics.